97 Effects of alkalization treatment on chemical composition and in vitro ruminal fermentation of anaerobically stored rice stover. (30th November 2020) - Ma, Yulin; Chen, Xu; Xiao, Jianxin; Liu, Shuai; Wang, Jingjun; Cao, Zhijun
Abstract: The objective of this trial was to evaluate the effects of urea and calcium hydroxide on the chemical composition and in vitro ruminal fermentation of rice stover. Rice stover was stored in polyethylene bags (35 × 25 cm, 350g per bag) with: (i) no additive (CON); (ii) 4% calcium hydroxide (CA, dry matter (DM) basis); (iii) 2.5% urea and 4% calcium hydroxide (UCA, DM basis); and (iv) 9% corn steep liquor and 2.5% urea and 4% calcium hydroxide (CUCA, DM basis). Dry matter were kept at the same level at 55% for all treatments. Totally, 36 bags (4 treatments × 3 store periods × 3 repeats) were prepared and stored at ambient temperature (25 ± 3 °C). The chemical composition was measured at day 7, 10 and 15 after storage. And the in vitro ruminal fermentation was tested in vitro at d 15. Date was subjected to two-way analysis of variance (ANOVA) with the fixed effects of treatments, times and treatments × times by using SPSS 24.0. All alkali treatments reduced neutral detergent fiber (NDF) and acid detergent fiber (ADF) content (P < 0.05), and increased the in vitro DM digestibility (IVDMD) of the rice stover compared with the CON. The in vitro NDF degradability (IVNDFD) and ADF degradability (IVADFD) were increased in UCA and CUCA rice stover (P < 0.05) compared to others. The highest acetic acid (AA), propionic acid (PA), butyric acid (BA), total volatile acids (TVFA) concentrations and 48-h cumulative gas production were observed in CUCA rice stover (P < 0.05). With the delay of storage time, dry matter (DM) and crude protein (CP) were decreased in CA and CUCA groups (P < 0.05). Results in this study suggested that 9% corn steep liquor and 2.5% urea and 4% calcium hydroxide might be an effective treatment combination.